2015
DOI: 10.1371/journal.pone.0145170
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Genetic Variants in Cancer-Related Genes between Chinese Hui and Han Populations

Abstract: BackgroundThe Chinese Hui population, as the second largest minority ethnic group in China, may have a different genetic background from Han people because of its unique demographic history. In this study, we aimed to identify genetic differences between Han and Hui Chinese from the Ningxia region of China by comparing eighteen single nucleotide polymorphisms in cancer-related genes.MethodsDNA samples were collected from 99 Hui and 145 Han people from the Ningxia Hui Autonomous Region in China, and SNPs were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Differences in the frequencies of genetic polymorphisms according to ethnics have been reported. Tian, et al 28 reported the genetic diversity of many SNPs in cancer-related genes between Chinese Hui and Han populations. Inoue, et al 29 also showed a difference in the frequency distribution of the genetic polymorphisms in the CYP1A1 and CYP1B1 gene in Japanese and Caucasian populations.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the frequencies of genetic polymorphisms according to ethnics have been reported. Tian, et al 28 reported the genetic diversity of many SNPs in cancer-related genes between Chinese Hui and Han populations. Inoue, et al 29 also showed a difference in the frequency distribution of the genetic polymorphisms in the CYP1A1 and CYP1B1 gene in Japanese and Caucasian populations.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al systemically investigated the effects of exogenous additives on the genetic diversity of drug absorption, distribution, metabolism and excretion between the Han majority and Hui minority in Northwest China and reported significant differences between the Han and Hui populations 28 . Our previous study also showed that the distribution of genetic variants in cancer‐related genes varies between Han and Hui people 24 . These studies highlight that genetic background diversity in ethnicities, such as the Han and Hui populations, may affect an individual's cancer spectrum.…”
Section: Discussionmentioning
confidence: 85%
“…Most Hui people are Muslims and descendants of soldiers, merchants and political emissaries from Arabia and Persia. 22 Approximately 2.2 million Hui people, who are characterised by religious purity, group identity and different living habits, 23,24 live in the Ningxia region of Northwest China, which has the highest incidence and mortality of GC. In this study, compared with Han patients, Hui patients were less likely to smoke or consume alcohol, but they were more likely to present at a more advanced T stage, N stage and clinical staging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation